ANALISIS KESULITAN BELAJAR MATEMATIKA MATERI PECAHAN PADA SISWA KELAS V SDN PUCUNG III - Ratih Lailathi Prajamukti; Prasetyono, Hendro (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to identify learning difficulties and factors that influence mathematics learning difficulties among students in class VC at SDN Pucung III. This study uses a qualitative descriptive approach. The research subjects are students in class VC at SDN Pucung III, with a total of 41 students. From this number, five students who have difficulty learning mathematics were selected using snowball sampling. Data collection was conducted through direct observation during the learning process in the classroom to identify the learning problems experienced by the students, as well as in-depth interviews with the students, teachers, and parents to obtain a more comprehensive picture. In addition, documents such as learning outcome reports and teachers' daily notes were reviewed to supplement the information. The conclusion of this study is that students in class VC at Pucung III Public Elementary School experience serious difficulties in learning mathematics, especially in the area of fractions related to solving addition and subtraction problems. Problems arise when they try to understand the relationship between fractions with different denominators. Both external and internal factors play a major role in driving these challenges. To help address such difficult situations, group remedial methods with innovative strategies can be applied to build a positive atmosphere to increase their motivation to learn.